PELAKSANAAN PROGRAM PARENTING DI LEMBAGA PAUD KECAMATAN BASA AMPEK BALAI TAPAN - Fifi Dwi Ningsih; Nasirun Nasirun; Yulidesni Yulidesni (Jurnal Ilmiah POTENSIA, 2018)
The problem in this research is how the implementation of a parenting program in early childhood education institutions in Sub Bases Ampek Tapan Hall. The purpose of this study to describe the implementation of a parenting program in early childhood education institutions in Sub Bases Ampek Tapan Hall. The method used quantitative descriptive. Subjects of this study is the head of the school as much as 6 class teachers and parents as much as 30 to 56 people in implementing early childhood parenting program. The data collection technique using a structured questionnaire. Analysis of data using statistical analysis with a percentage formula. The results showed that the implementation of a parenting program in early childhood institutions Hall Tapan District of Bases Ampek average to very good. It is therefore recommended to the school that has implemented a program with good parenting is expected to maintain and improve the implementation of parenting programs in the school. For the next researcher suggested considering this study implementation of growth and development of children.      The problem in this research is how the implementation of a parenting program in early childhood education institutions in Sub Bases Ampek Tapan Hall. The purpose of this study to describe the implementation of a parenting program in early childhood education institutions in Sub Bases Ampek Tapan Hall. The method used quantitative descriptive. Subjects of this study is the head of the school as much as 6 class teachers and parents as much as 30 to 56 people in implementing early childhood parenting program. The data collection technique using a structured questionnaire. Analysis of data using statistical analysis with a percentage formula. The results showed that the implementation of a parenting program in early childhood institutions Hall Tapan District of Bases Ampek average to very good. It is therefore recommended to the school that has implemented a program with good parenting is expected to maintain and improve the implementation of parenting programs in the school. For the next researcher suggested considering this study implementation of growth and development of children.